Pemanfaatan Konseling Keluarga Eksperensial untuk Penyelesaian Kasus Kekerasan dalam Rumah Tangga - Afdal Afdal (Indonesian Institute for Counseling, Education and Therapy (IICET), 2015)
Domestic Violence is defined as any act against someone, especially women, misery or suffering physical, sexual, psychological, and / or negligence of household including threat to commit acts, coercion or deprivation of liberty unlawfully in the domestic sphere, which includes physical violence, psychological violence, sexual abuse and neglect household. In addition to alleviating the problem through legal means, other things that can be done is through family counseling through experiential approach. Therapeutic family counseling experiential deemed suitable for this case due to various reasons, including this therapy is a humanistic, promote communication and creativity counselors, using the role of counselor and koterapis, and in accordance with Indonesian culture better not choose the path of law to tackle these cases (for some reason including the desire for the unity of the family, the attitude of shame known to many people and so on)